Various Malignancies Amongst Children Presenting to Pediatric Unit of Tertiary Care Center - Aneeka Zia, Afsheen Batool Raza, Novera Khalid (Pakistan Journal of Medical & Health Sciences, 2024)
Childhood malignancies are slowly rising critical medical issue with low rate of survival. Despite of its variability in frequency and distribution with respect to its types, very few studies have addressed this aspect in Pakistan. In order to understand the factors to help in management and increase success rate of treatment, frequency and patterns of different types of malignancies in our settings should be understood well. Aim and Objective: To find out the frequency of various malignancies amongst children presenting to pediatric unit of tertiary care center. Materials and Methods: This descriptive cross sectional study was conducted in pediatric unit of Jinnah Hospital, Lahore, between 08-04-2021 to 08-04-2022 on 240 children. The data was collected using non-probability consecutive sampling after taking consent from the parent/guardian of the patient. Socio-demographic and clinical data was collected on a semi-structured proforma and was analyzed using SPSS v.17. Mean, Standard deviation, frequency and percentages were given for quantitative and qualitative data respectively while Chi Square test was used to find association of types of cancers with age and gender keeping a p-value<0.05 as significant. Results: The mean age of children was 8.05 ± 4.077 years with 53.8% males. Acute leukemia (20.8%) was the commonest type of malignancy among other including Burkitt lymphoma in 18.8%, Rhabdomyosarcoma in 18.3, Non Hodgkin lymphoma in 9.2%,Hodgkin lymphoma in 7.1%,Wilms tumor in 14.2%,Neuroblastoma in 5%, Retinoblastoma in 3.3% and Yolk sac tumor in 3.3% children. Only Rhabdomyosarcoma and Acute leukemia had significant association with age groups (p-values= 0.043 & 0.014 respectively). Conclusion: This study concludes that acute leukemia was commonest observed type of childhood malignancy (20.8%), whereas Retinoblastoma and Yolk sac tumor were the least observed ones. Only age was associated with Rhabdomyosarcoma and Acute leukemia among all types of malignancies. Keywords: Childhood malignancies, Age group, Acute leukemia, Rhabdomyosarcoma, Retinoblastoma